Breast feeding, obesity, and asthma association: clinical and molecular views - Naghmeh Kian; Alireza Bagheri; Fardis Salmanpour; Afsaneh Soltani; Zahra Mohajer; Noosha Samieefar; Behzad Barekatain; Roya Kelishadi (Clinical and Molecular Allergy, 2023)
Abstract Asthma is a chronic condition that affects children worldwide. Accumulating number of studies reported that the prevalence of pediatric obesity and asthma might be altered through breastfeeding. It has been proposed that Leptin, which exists in human milk, is oppositely associated with weight increase in newborns. It may also influence peripheral immune system by promoting TH1 responses and suppressing TH2 cytokines. Leptin influences body weight and immune responses through complex signaling pathways at molecular level. Although previous studies provide explanations for the protective role of breastfeeding against both obesity and asthma, other factors such as duration of breastfeeding, parental, and prenatal factors may confound this relationship which requires further research.